Youth media literacy in interpreting the ideology of the film documentary The Malayan Emergency (2010) - Loh, Yoke Ling; Mohd. Nor Shahizan Ali,; Normah Mustaffa, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Ideology dissemination via historical documentaries provide an advantage to the government in implementing national policies. The characteristics of documentary films which represent 'reality' allow varied interpretations to reach their target audiences. It is thus imperative that the audience's understanding and interpretation be parallel with the ideology that the government wants to convey as to avoid the misinterpretation of information. However, studies have shown that audiences' interpretations are not always in line with what the producer intends to communicate. As such, the objective of this research is to analyse factors affecting youth media literacy in understanding and interpreting the ideology of historical documentary films titled The Malayan Emergency (2010). Audiences especially youths have their own views and opinions on any documentary film they watch. Experimental results show that critical thinking, media aesthetics and the exposure to the Internet actually affect ideological interpretations in historical documentary films. Among others, the results of the experimental study also showed that cognitive thinking skills and education backgrounds of youth have influenced the interpretation and understanding of historical documentary films. The interpretation and understanding of youth in ideology towards historical documentary films are influenced by individual factors (educational background and cognitive thinking), media texts (media aesthetic) and external factors (exposure to Internet). Thus, individual factors are the key aspect of media literacy to interpret messages critically.